Hubungan Kunjungan ANC, Kepatuhan Konsumsi Tablet FE dan Status Gizi dengan Kejadian Anemia pada Ibu Hamil Trimester III di Puskesmas Kutaraya Kecamatan Kota Kayuagung Kabupaten Ogan Komering Ilir - Nengah Wirke; Eka Afrika; Helni Anggraini (Universitas Batanghari Jambi, 2022)
Anemia is a condition in which the body has too few red blood cells (erythrocytes), which red blood cells contain hemoglobin which functions to carry oxygen to all body tissues. During pregnancy the body will experience significant changes, the amount of blood in the body increases by about 20-30%, so it requires a supply of iron and vitamins to make hemoglobin (Hb) so that anemia does not occur. The purpose of this study was to determine the relationship between Antenatal Care Visits Frequency, Fe Tablet Consumption Compliance, and nutritional status simultaneously with the incidence of Anemia in Third Trimester Pregnant Women at Kutaraya Health Center, Kota Kayuagung District, Ogan Komering Ilir (OKI) Regency in 2021. This study used the type quantitative analytical survey research with a purpose sampling approach, this research was conducted at the Kutaraya Health Center, Kota Kayuagung District, Ogan Komering Ilir (OKI) Regency with 82 respondents. The results of the chi-square statistical test for ANC visits obtained value = 0.009, variable compliance with FE tablet consumption obtained value = 0.043, nutritional status variable obtained value = 0.001 smaller than = 0.05 indicating there is a significant relationship between ANC visits, compliance with FE tablet consumption and nutritional status with the incidence of anemia in third trimester pregnant women at Kutaraya Health Center, Kota Kayuagung District, Ogan Komering Ilir (OKI) Regency in 2021